A Study for the Depiction of Non Linear Differential Equations: Classification and Solution Methods for Differential Equations (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Differential equations are called fractional differential equations (pde) or normal differential equations (tribute) as indicated by whether they contain incomplete derivatives. The order of a differential equation is the highest order derivative happening. An answer (or specific arrangement) of a differential equation of order n comprises of a capacity characterized and n times differentiable on an area D having the property that the useful equation gotten by substituting the capacity and its n derivatives into the differential equation holds for each point in D. In this paper classification of differential equation is done and finite difference method is additionally introduced.